Digital transformation for improving sustainable value of products and services from agri-food systems - Silva, Roosevelt Fabiano Moraes da; Papa, Matheus; Bergier, Ivan; Oliveira, Stanley Robson Medeiros de; Cruz, Sergio Aparecido Braga da; Romani, Luciana Alvim Santos; Massruhá, Silvia Maria Fonseca Silveira (Frontiers in Sustainability, 2022)
Value is routinely concentrated at the final links of food production chains as a consequence of market failures or asymmetries that distribute wealth unevenly in agri-food supply systems. Otherwise, for products with a geographic origin, the share can be more equitably distributed by adding environmental, sociocultural or technological values to products associated with sustainable models. Protecting a geographic indication (GI) of value-added products requires complex collective rules of sui generis systems, certified trademarks or business practices, including the approval of protocols or even unfair protection suitlaws. These rules are created on multilevel legislations gathering intrinsic cultural, historical and economic features. As a result, GI schemes are typically costly thus preventing access of general smallholders in product-valued chains. Digital technologies like mobile applications have a promising role in minimizing these limitations along food production chains, from pre-production to production and post-production. The pervasive spread of mobile devices with useful built-in sensors can be therefore a major consequence of the digital transformation in agriculture by means of intuitive applications combined with high-level technologies such as cloud/edge computing and Application Programming Interfaces (APIs). In this article, we present a new perspective on the digital transformation of the agri-food sector that may fasten smallholders' inclusion and access in market ecosystems of value-added products with GI. Such perspective demands the understanding of stakeholders networks for customizing mobile applications for digital authentication of product GI. The approach can foster new compliance schemes as those embedded in Environmental, Social and Governance (ESG) market initiatives.